CD4+ T cell heterogeneity in gestational age and preeclampsia using single-cell RNA sequencing - Tsuda, Sayaka; Shichino, Shigeyuki; Tilburgs, Tamara; Shima, Tomoko; Morita, Keiko; Yamaki-Ushijima, Akemi; Roskin, Krishna; Tomura, Michio; Sameshima, Azusa; Saito, Shigeru; Nakashima, Akitoshi (Frontiers in Immunology, 2024)
A balance between pro-inflammatory decidual CD4+ T cells and FOXP3+ regulatory T cells (FOXP3+ Tregs) is important for maintaining fetomaternal tolerance. Using single-cell RNA-sequencing and T cell receptor repertoire analysis, we determined that diversity and clonality of decidual CD4+ T cell subsets depend on gestational age. Th1/Th2 intermediate and Th1 subsets of CD4+ T cells were clonally expanded in both early and late gestation, whereas FOXP3+ Tregs were clonally expanded in late gestation. Th1/Th2 intermediate and FOXP3+ Treg subsets showed altered gene expression in preeclampsia (PE) compared to healthy late gestation. The Th1/Th2 intermediate subset exhibited elevated levels of cytotoxicity-related gene expression in PE. Moreover, increased Treg exhaustion was observed in the PE group, and FOXP3+ Treg subcluster analysis revealed that the effector Treg like subset drove the Treg exhaustion signatures in PE. The Th1/Th2 intermediate and effector Treg like subsets are possible inflammation-driving subsets in PE.